PENGARUH ROE DAN EPS TERHADAP HARGA SAHAM PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BEI TAHUN 2018-2020 - George Den Paulsen Sagala; Paul Eduard Sudjiman (Jurnal Ekonomis, 2022)
This study aims to examine the effect of ROE dan EPS on stock Prices. This study uses a sample of food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the 2018-2020 period. The number of food and beverage companies that were used as research samples were 17 companies for 3 years using purposive sampling method. This study uses secondary data from the annual financial statements of food and beverage companies for 2018-2020. The result of the partial analysis show tha ROE has no sifnificant effect on stock prices, EPS has a significant effect on stock prices. Simultaneously shows that there si a significant effect between ROE and EPS on stock prices.